2023
DOI: 10.1101/2023.01.10.523356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome based multivalent vaccine: achieving potent immunization, broadened reactivity, and strong T cell responses with nanograms of proteins

Abstract: Exosome based vaccines represent an interesting opportunity in the pandemic time we live. Compared to the available vaccines, an exosome-based vaccine may answer to the need of efficacy and increased safety. Here, we used exosomes to deliver a "cocktail" protein-based vaccine, in which two independent viral proteins are delivered using the exosome membrane as carrier. Cells were engineered to express either SARS-CoV-2 Delta spike (StealthTM X-Spike, STX-S) or nucleocapsid (StealthTM X-Nucleocapsid, STX-N) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the percentage of exosomes that displayed these morphologically recognizable spikes was a small minority of the exosomes, no more than 10% of the total exosome population. Thus, while these Spike/delta-CSM-2P-ΔC-ERES-containing exosomes are immunogenic( 37 ), they are by no means reflective of optimized exosome engineering.…”
Section: Resultsmentioning
confidence: 99%
“…However, the percentage of exosomes that displayed these morphologically recognizable spikes was a small minority of the exosomes, no more than 10% of the total exosome population. Thus, while these Spike/delta-CSM-2P-ΔC-ERES-containing exosomes are immunogenic( 37 ), they are by no means reflective of optimized exosome engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, formulation of spike + nucleocapsid with cationic or anionic lipids showed that this combination of antigens induced IgG and IgA antibodies and production of IL-5 and IFN-γ [86]. Biotechnological approaches have also been employed, such as the generation of exosomes decorated with spikes (STX-S) or nucleocapsids (STX-N) [90]. These approaches led to improved immune responses, particularly with the combination of S + N. Another strategy in development involves fusing the most immunogenic regions of different SARS-CoV-2 proteins, resulting in a protein fusion called "SpiN" [91].…”
Section: Combination Of Nucleocapsid and Spike Recombinantmentioning
confidence: 99%